2020
DOI: 10.17586/2220-8054-2020-11-2-237-245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and concentration dependant antibacterial potentials of nickel oxide nanoparticles against Staphylococcus aureus and Escherichia coli

Abstract: Bacterial resistance to antibiotic treatment is a major emerging clinical and public health issue across the globe. Advancements in the field of metal oxide nanomaterials in the last few years have improved the potential of metal oxides in different applications. Metal oxides, of which, nickel oxide (NiO) is one, also possess antibacterial activities. This investigation was planned to synthesize NiO nanoparticles to study their antibacterial potential in comparison with bulk NiO and standard antibiotics at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Another study found that the second most frequently isolated AMR bacteria from Saudi hospitals were K. pneumoniae , with a significant percentage being ESBL-positive [ 16 ]. As a result, clinicians have had to consider treatment regimens based on combinations of medications with inadequate activity or to reuse some old and abandoned antimicrobials, such as colistin, that are known to have several adverse reactions [ 17 , 18 , 19 , 20 ]. As a result, the development of novel antimicrobial agents is critically warranted to fight these microorganisms with minimal and tolerated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that the second most frequently isolated AMR bacteria from Saudi hospitals were K. pneumoniae , with a significant percentage being ESBL-positive [ 16 ]. As a result, clinicians have had to consider treatment regimens based on combinations of medications with inadequate activity or to reuse some old and abandoned antimicrobials, such as colistin, that are known to have several adverse reactions [ 17 , 18 , 19 , 20 ]. As a result, the development of novel antimicrobial agents is critically warranted to fight these microorganisms with minimal and tolerated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial activity of pure-NiO nanoparticles against Gram-negative bacteria (Pseudomonas aeruginosa, Escherichia coli) and Gram-Positive bacteria (Staphylococcus aureus, Streptococcus pneumonia) has been reported (Baek and An, 2011). NiO nanoparticles were found better antibacterial agents than tetracycline and gentamicin antibiotics against Gram-negative and Gram-positive bacteria (Gupta et al, 2020a). The antibacterial activity of NiO nanoparticles using different antimicrobial and biophysical studies revealed that these nanoparticles have stronger antibacterial activity against Gram-positive bacteria compared to Gram-negative bacteria (Behera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%